2022
DOI: 10.1186/s12913-022-08311-9
|View full text |Cite
|
Sign up to set email alerts
|

Disaster preparedness knowledge and its relationship with triage decision-making among hospital and pre-hospital emergency nurses - Ardabil, Iran

Abstract: Background Hospital and pre-hospital emergency nurses are at the forefront of disaster response. Disaster incidents continue to pose a threat to healthcare systems by exposing them to an overwhelming surge of patients. Methods This descriptive cross-sectional study was performed on 472 hospital and pre-hospital emergency nurses in Ardabil province, in the northwest Iran, from March to April 2021, were recruited by convenience sampling method. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 44 publications
1
8
0
1
Order By: Relevance
“…with 142 nurses working in six Public Health Centers in Pangandaran, Indonesia, it was determined that more than half of the participants had a high level of disaster preparedness (Emaliyawati et al, 2021). Similarly, several studies have reported varied levels of preparedness of nurses for disasters (Azizpour et al, 2022;Martono et al, 2019). The literature reports that PFA training should be provided to nurses to better prepare them for disaster situations and improve response quality (Kılıç & Şims ¸ek, 2019;Said et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…with 142 nurses working in six Public Health Centers in Pangandaran, Indonesia, it was determined that more than half of the participants had a high level of disaster preparedness (Emaliyawati et al, 2021). Similarly, several studies have reported varied levels of preparedness of nurses for disasters (Azizpour et al, 2022;Martono et al, 2019). The literature reports that PFA training should be provided to nurses to better prepare them for disaster situations and improve response quality (Kılıç & Şims ¸ek, 2019;Said et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In explaining this finding, it seems that the lack of trained volunteers in disasters is a big challenge for healthcare systems worldwide, especially in low-income countries. As studies indicate, preparedness comes with higher knowledge and skills, which in turn help to cope with disasters ( 26 ). Trained volunteers can prove beneficial by transferring knowledge and experiences to local communities and improving public awareness concerning the management of various crises or disasters ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although emergency medical services systems may differ between nations and areas, their essential objective of providing prompt and efficient medical care in emergencies remains the same. These treatments are essential to save lives, lessen the effects of injuries, and improve patient outcomes [ 23 ].…”
Section: Reviewmentioning
confidence: 99%